CONFIGURATION OF PUMPS IN SERIES OR PARALLEL INSTALLATIONS: DELIVERY CAPACITY ENHANCEMENT - Tibay, Edgar U (Journal of Agriculture and Technology Management, 2015)
The challenge of today’s engineers is to find the most efficient way to operate a pump by increasing its delivery head and its discharge flow in every given condition. Configurations of pumps in series, parallel and single installations were compared and studied for eventual developments in pumping systems, technologically and economically beneficial for future pumping applications in domestic, industrial, agricultural and re-creational use. The study evaluated the effect and delivery of the single pump and the configuration in series and parallel arrangement of the units of equal geometric characteristics. The performance of the delivery discharge and head and the best arrangement or configuration of the pumping units for an optimum capacity enhancement was determined. Results of the study show that the pumps configured in series and parallel statistically increased their respective capacities in terms of static delivery head and discharge volume flow, respectively.